1999
DOI: 10.1093/humrep/14.3.671
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcome after in-vitro fertilization-surrogacy

Abstract: The perinatal outcome of pregnancies (both single and multiple) established after in-vitro fertilization (IVF)-surrogacy was evaluated and compared to the outcome of pregnancies that resulted from standard IVF. Analysis of medical records and a telephone interview with physicians, IVF-surrogates, and commissioning mothers were conducted to assess prenatal follow up and delivery care in several hospitals. 95 IVF-surrogates delivered 128 liveborn (65 singletons, 27 sets of twins and two sets of triplets). The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 23 publications
4
47
0
1
Order By: Relevance
“…In a study comparing the perinatal outcome of pregnancies (both single and multiple) established after in-vitro fertilisation (IVF)esurrogacy with the outcome of pregnancies resulting from standard IVF [41], there was general reassurance regarding perinatal outcome. The incidence of malformation was similar to those reported for the general population.…”
Section: Prenatal and Neonatal Complicationsmentioning
confidence: 99%
“…In a study comparing the perinatal outcome of pregnancies (both single and multiple) established after in-vitro fertilisation (IVF)esurrogacy with the outcome of pregnancies resulting from standard IVF [41], there was general reassurance regarding perinatal outcome. The incidence of malformation was similar to those reported for the general population.…”
Section: Prenatal and Neonatal Complicationsmentioning
confidence: 99%
“…Most case series report no increase in adverse events related to surrogate pregnancy. 10,[18][19][20][21][22] However, in a recent report, 2 of 9 surrogate mothers underwent postpartum hysterectomy: after a delivery of triplets with placenta accreta and after uterine rupture that occurred during delivery of a macrosomic infant. 23 The limited amount of evidence about the risks associated with surrogate pregnancy has 2 implications: (a) health care providers should have a high index of suspicion for complications and a low threshold for investigations and referral to higher levels of care; and (b) if complications occur, health care providers should report the complications to the centre that initiated the pregnancy so that surrogacy outcomes can be tracked and a better evidence base can be built.…”
Section: Prenatal Care Of the Surrogatementioning
confidence: 99%
“…10,21,22 The evidence is limited, but perhaps these theoretical concerns are not clinically relevant. An alternative explanation for the discrepancy between expert opinion and clinical experience is that thorough counselling before conception reduces psychological risk.…”
Section: Prenatal Care Of the Surrogatementioning
confidence: 99%
“…Clues on the transplantation technique and improvements in immunosuppressive agents have enabled progression to the clinical research phase in the last two decades (8,9). Currently, uterine factor infertility patients can conceive through gestational surrogacy (10). Other indications of gestational surrogacy are history of recurrent miscarriage and implantation failure and deteriorating maternal diseases such as severe systemic lupus erythematosus, cardiac disorders, Takayasu's arteritis, history of breast cancer, hematological condition, pulmonary hypertension, residual pituitary macroadenoma, and brain tumor (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, uterine factor infertility patients can conceive through gestational surrogacy (10). Other indications of gestational surrogacy are history of recurrent miscarriage and implantation failure and deteriorating maternal diseases such as severe systemic lupus erythematosus, cardiac disorders, Takayasu's arteritis, history of breast cancer, hematological condition, pulmonary hypertension, residual pituitary macroadenoma, and brain tumor (10,11). Results of many studies have shown that children born through vital organ tissue transplantation and immunosuppression or gestational surrogacy are healthy (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%